DYLEMATY MIĘDZYNARODOWEJ ODPOWIEDZIALNOŚCI PAŃSTW - Zbaraszewska, Anna (Wydział Prawa i Administracji UAM, 2007)
At its fifty-third session (2001), the International Law Commission (ILC) finally adopted a complete text of the Draft Articles on the Responsibility of States for Internationally Wrongful Acts. The purpose of those Draft Articles is to define “the secondary rules” which are aimed at determining the legal consequences of a failure to fulfill the obligations established by “the primary rules”. This paper attempts to assess the final results of the ILC’s codification works which had taken nearly 50 years. The term “international responsibility” covers the new legal relations which arise under international law by reason of the internationally wrongful act of a state. They occur between a state which has committed such an act and an injured state or states. An internationally wrongful act of a state occurs when conduct consisting of an action or its omission is attributable to the state under international law and constitutes a breach of an international obligation of that state. The content of new rights and obligations is specified in Part Two (Content of the International Responsibility) and Part Three (Implementation o f the International Responsibility) of the Draft Articles. The obligations of the responsible state to cease the wrongful conduct if it is continuing; to offer appropriate assurances and guarantees of non-repetition if circumstances so require, and to make full reparation for the injury caused are the core legal consequences of an internationally wrongful act. A serious breach of an obligation arising under a peremptory norm of general international law may entail further consequences. In the event of a serious breach of ius cogens rules all states are obliged to cooperate in order to bring such a breach to an end, not to recognize as lawful the situation created by that act and not to render aid or assistance to the responsible state to maintain the situation so created. The implementation of state responsibility is, in the first place, an entitlement of “the injured state”. This concept refers to the state whose individual right has been infringed by the internationally wrongful act or which has been particularly affected by it. In case of breaches of obligations protecting the collective interests of a group of states or the international community as a whole, responsibility may be invoked by states which are not themselves “injured” in the sense of Article
DILEMMAS OF THE INTERNATIONAL RESPONSIBILITY OF STATES